Comparison of the outcomes between blended learning and traditional pronunciation course in the EFL context - Ting, Xiao; Abdul Kadir , Zaemah; Syed Husain, Sharifah Shahnaz (Journal of Islamic, Social, Economics and Development, 2025)
This study investigates the comparative effectiveness of Blended Learning (BL) and traditional instructional methods in an English as a Foreign Language (EFL) pronunciation course in China. Despite the growing adoption of BL, its impact on specific outcomes in pronunciation instruction relative to traditional teaching remains underexplored. The research employed a comparative design with the freshman students, assessing three core dimensions: learner satisfaction, student engagement (behavioral, cognitive, and emotional), and course outcomes (grades, online activities, attendance, and dropout rates). The results indicated that the BL approach led to significantly higher levels of learner satisfaction and overall student engagement across all three sub-dimensions compared to the traditional classroom. Regarding course outcomes, while both groups showed significant improvement in pronunciation test scores from pre-test to post-test, the BL group demonstrated a substantially greater gain. Furthermore, the BL group significantly outperformed the traditional group in online activity scores and attendance. However, no statistically significant difference was found in dropout rates between the two instructional methods. The study concludes that the blended learning model is more effective than the traditional approach in enhancing student satisfaction, engagement, and key learning outcomes in an EFL pronunciation context. These findings provide empirical evidence supporting the integration of BL in pronunciation teaching, while also highlighting the need for thoughtful course design to maximize its benefits and address variations in student satisfaction and engagement.